Pengaruh Motivasi dan Budaya Organisasi terhadap Work-Life Balance: Studi Kasus Pekerja yang Menjadi Anggota Suporter the Jakmania Ciledug, Kota Tangerang - Muhammad Daffa; Setyani Dwi Lestari (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Football supporters are often referred to as the "12th player" due to their crucial role in creating a lively match atmosphere and boosting players' morale. Nearly every province or city in Indonesia has its own football club and a passionate fanbase. Notable examples include The Jakmania (supporters of Persija Jakarta), Bobotoh (Persib Bandung), and Bonek (Persebaya Surabaya). The challenges faced by these supporters extend beyond organizational involvement and relate closely to their ability to manage and allocate time effectively between work and non-work domains. For members of The Jakmania who are also employed, balancing professional responsibilities, personal life, and supporter-related activities has become a significant issue. This study aims to examine the influence of Motivation (X1) on Work-Life Balance (Y), as well as the influence of Organizational Culture (X2) on Work-Life Balance (Y) among working members of The Jakmania Ciledug, Tangerang City. The research utilized probability sampling through a simple random sampling method to ensure randomness and avoid selection bias, thereby enhancing the representativeness of the sample. The total population consisted of 112 members, and using the Slovin formula, a final sample of 53 respondents was determined. The analysis was conducted using multiple linear regression, assisted by SPSS version 25 and Microsoft Excel 2017. The findings reveal that Motivation (X1) has a positive and significant influence on Work-Life Balance (Y), and Organizational Culture (X2) also has a positive and significant influence on Work-Life Balance (Y).